Glass Crash Feeling : Goldrausch 2010. - Effinger, Birgit; Goldrausch Künstlerinnenprojekt Frauennetzwerk Berlin e.V., Berlin; Kruse, Hannah (Berlin : Argobooks, 2010)
Norkeit, Lätitia ; Kollowa, Katja ; Myga Kasten, Anna ; Rave, Bettina ; Franke, Linda ; Echeverri Fernandez, Tatiana ; Curnier Jardin, Pauline ; Clarke, Elly ; Steinhauser, Miriam ; Scheper, Karen ; Greiner, Anne Kathrin ; Ward, Kym ; Marzall, Silvia ; Jugert, Lisa ; Letelier, Michelle-Marie
Glass Crash Feeling. Goldrausch 2010, Galerie September - Galerie Barbara Thumm, Berlin, 20.11. - 19.12.2010
boek